Animal Models for Tuberculosis in Translational and Precision Medicine - Zhan, Lingjun; Tang, Jun; Sun, Mengmeng; Qin, Chuan (Frontiers in Microbiology, 2017)
Tuberculosis (TB) is a health threat to the global population. Anti-TB drugs and vaccines are key approaches for TB prevention and control. TB animal models are basic tools for developing biomarkers of diagnosis, drugs for chemotherapy, and researching pathogenic mechanisms for identification of targets; thus, they serve as the cornerstone of comparative medicine, translational medicine and precision medicine. In this review, we discuss the current use of TB animal models and their problems, as well as offering perspectives on the future of these models.